Serine proteases of the complement lectin pathway and their genetic variations in ischaemic stroke. Issue 2 (18th July 2017) - Tsakanova, Gohar; Stepanyan, Ani; Nahapetyan, Karen; Sim, Robert B; Arakelyan, Arsen; Boyajyan, Anna
Abstract : Aims: The aim of the current study was to assess the proteolytic activities of collectin-bound MASP-1 and MASP-2 in the blood of patients with ischaemic stroke, as well as the association of their six genetic polymorphisms (rs3203210, rs28945070, rs28945073 in MASP1 gene and rs2273343, rs12711521, rs147270785 in MASP2 gene) with this pathology. Methods: In total, 250 patients and 300 healthy subjects were involved in this study. MBL-associated serine protease (MASP)-1 and MASP-2 activities were measured using in-house developed immunofluorescent and enzyme-linked immunosorbent assays, respectively. Sequence specific primer PCR was used to study the association of MASP1 and MASP2 genetic polymorphisms with ischaemic stroke. Results: The results obtained demonstrate that the activities of collectin-bound MASP-1 and MASP-2 in patients with ischaemic stroke are significantly higher than those in healthy subjects (p<0.001). According to the data obtained for genotyping, the rs3203210 polymorphism in the MASP1 gene and the rs147270785 polymorphism in the MASP2 gene are associated with ischaemic stroke (p<0.0001). Conclusions: In conclusion we suggest that the complement lectin pathway serine proteases, MASP-1 and MASP-2, can be associated with ischaemic stroke development risk and may participate in pathological events leading to post-ischaemic brain damage. Moreover rs3203210 and rs147270785 single nucleotide polymorphisms in the MASP1 and MASP2 genes, respectively, are strongly associated with ischaemic stroke, and the minor rs3203210*C and rs147270785*A alleles of these polymorphisms may be considered as protective factors for ischameic stroke, at least in the Armenian population.